Developing Proper Systems for Successful Cloud Computing Implementation Using Fuzzy ARAS Method (Case Study: University of Tehran Faculty of New Science and Technology) - Jalil Heidaryd Dahooie; Navid Mohammadi; AmirSalar Vanaki; mohsen Jamali (Journal of Information Technology Management)
Given the increasing requirements of communication and the need for advanced network-based technologies, cloud computing has been suggested as a perfect strategy to achieve these objectives. Yet, despite the development of computing applications and the increased number of alternatives, it is quite a difficult task to select the exact software platform for the implementation of cloud computing arrangements. In this line, the present paper aimed to develop a scientific framework as how to select the proper software for successful cloud computing implantation at the infrastructure level. First through a review on the related literature and using experts’ opinions, the software selection criteria were extracted. Based on the framework proposed here, the interval-valued fuzzy ARAS method was then employed for weighting and prioritizing specified alternatives. This model was applied by the Faculty of New Sciences and Technologies of Tehran University in order to select proper software platforms from among five alternatives. The results revealed that the OpenStack cloud operating system has been selected as the best alternative, most probably because this platform demonstrates significant achievement for its merits such as high level of performance, reliability and security, stability, and usability.